INTENTIONAL APES BEHAVIOR - Iwona Olejniczak (Filozofia i Nauka, 2019)
The main topic of this article is apes’ intentional behaviour. I consider the Michael Tomasello’s concept of intentionality. I outline how different levels of intentionality presented by Tomasello could be applied to apes’ behaviour. To do so I examine few experiments and observations (in natural conditions) of apes’ behaviour and try to apply Tomasello’s intentionality concepts. My main concern is the possibility of group and shared intentionality in ape communities, which could suggest that there is some kind of culture oriented behaviour in non-human animals.